Digital PCR analysis of circulating tumor DNA: a biomarker for chondrosarcoma diagnosis, prognostication, and residual disease detection. (23rd August 2017) - Gutteridge, Alice; Rathbone, Victoria M.; Gibbons, Rebecca; Bi, Mark; Archard, Nicholas; Davies, Kate E. J.; Brown, Jake; Plagnol, Vincent; Pillay, Nischalan; Amary, Fernanda; O'Donnell, Paul; Gupta, Manu; et al.
Abstract: Conventional chondrosarcoma is the most common primary bone tumor in adults. Prognosis corresponds with tumor grade but remains variable, especially for individuals with grade (G) II disease. There are currently no biomarkers available for monitoring or prognostication of chondrosarcoma. Circulating tumor DNA (ctDNA) has recently emerged as a promising biomarker for a broad range of tumor types. To date, little has been done to study the presence of ctDNA and its potential utility in the management of sarcomas, including chondrosarcoma. In this study, we have assessed ctDNA levels in a cohort of 71 patients, 32 with sarcoma, including 29 individuals with central chondrosarcoma (CS) and 39 with locally aggressive and benign bone and soft tissue tumors, using digital PCR. In patients with CS, ctDNA was detected in pretreatment samples in 14/29 patients, which showed clear correlation with tumor grade as demonstrated by the detection of ctDNA in all patients with GIII and dedifferentiated disease ( n = 6) and in 8/17 patients with GII disease, but never associated with GI CS. Notably detection of ctDNA preoperatively in GII disease was associated with a poor outcome. A total of 14 patients with CS had ctDNA levels assessed at multiple time points and in most patients there was a clear reduction following surgical removal. This research lays the foundation for larger studies to assess the utility of ctDNA for chondrosarcoma diagnosis, prognostication, early detection of residual disease and monitoring disease progression. Abstract : Circulating tumor DNA (ctDNA) is emerging as a powerful biomarker for a range of cancers. The authors of this study have used digital PCR to assess the ability to detect ctDNA for the first time in patients with chondrosarcoma. ctDNA was detectable in 14 of 29 patients and its detection was associated with high‐grade disease and a significantly poorer prognosis compared to those patients in whom mutant IDH1 was not detected in cell free DNA.